The Effect of Inflation, Capital Structure, and ROA on Stock Returns in Food and Beverage Companies Listed on The Indonesia Stock Exchange in 2017-2020 - Wahyuningsih, Sri; Wiyono, Gendro; Maulida, Alfiatul (Invoice : Jurnal Ilmu Akuntansi, 2023)
This study aims to analyze the effect of inflation, capital structure, and ROA on stock returns in food and beverage companies listed on the IDX in 2017-2020. The sampling technique used in this study was purposive sampling method. The number of samples used in this study were 20 food and beverage companies listed on the Indonesia Stock Exchange in 2017-2020. The analytical method used in this research is multiple regression and the data is processed using SPSS. The hypothesis testing method uses a significant level of 0.05 (5%). The results of this study indicate that the inflation variable has a significant effect on stock returns, capital structure has no significant effect on stock returns, ROA has a significant effect on stock returns